Management and ethical decision-making - Robison, Wade L. (Journal of business ethics, 1984)
Every human activity has its characteristic features, the general tendencies that are often difficult to perceive for those engaged in the activity. Such general tendencies are of special concern to those managing in such activities, whether one is coaching soccer or running a corporation, for only with knowledge of such tendencies can one engage in intelligent managing and, more important, intelligent moral action. For the activity of business is not value-neutral, and if one is to manage morally in business, one must come to understand its general tendencies insofar as they affect values.